Epidemiological and clinical profile of Trypanosoma cruzi-HIV coinfection in a cohort of patients followed at the Evandro Chagas National Institute of Infectious Disease (INI) - Fiocruz - Hasslocher-Moreno, Alejandro Marcel (2021)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Laboratório de Pesquisa Clínica em Doença de Chagas. Rio de Janeiro, RJ, Brasil.